2021
DOI: 10.1016/j.jadohealth.2020.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in the Relationship Between Stressful Life Events and Quality of Life in Adolescents

Abstract: Stressful life events (SLEs) increase allostatic load and require adaptation. Experiencing SLEs has been associated with decreased health-related quality of life (HRQOL) among adolescents. This study examined racial/ethnic and developmental differences in the relationship between SLEs and HRQOL from preadolescence to midadolescence. Methods: Data were from 4,824 participants in the Healthy Passages project, a population-based prospective longitudinal survey of fifth, seventh, and 10th grade adolescents in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
4
8
1
Order By: Relevance
“…This work showed that negative life events had a negative impact on QoL, which was consistent with previous research results [10,20,43]. With the accumulation of negative life events, health gradually deteriorates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This work showed that negative life events had a negative impact on QoL, which was consistent with previous research results [10,20,43]. With the accumulation of negative life events, health gradually deteriorates.…”
Section: Discussionsupporting
confidence: 92%
“…Life events can increase the risk of depression [16,17], affect individual mental health [18], and reduce one's subjective well-being [19]. In recent years, a large number of studies [2,10,20 ] have shown that life events are signi cantly related to QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Families are considered partners in the care of other family members (5). The concept of family centered care is a philosophy in nursing that recognizes the very important role of the family in caring for family members who are sick (15).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the family in the care of family members in the hospital can affect the lives of other family members both physically, psychologically and socially (4). Families are considered partners in the care of other family members (5). The concept of family centered care is a philosophy in nursing that recognizes the very important role of the family in caring for family members who are sick (6) .…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Life events can increase the risk of depression ( 16 , 17 ), affect individual mental health ( 18 ), and reduce one's subjective well-being ( 19 ). In recent years, some studies ( 2 , 10 , 20 ) have shown that NLE are significantly related to QoL.…”
Section: Introductionmentioning
confidence: 99%